(untitled) (Zien Journal of Social Sciences and Humanities, 2025)
This article reflects the work done by the Russian Empire to conquer the Kokand Khanate, the organization of the Ferghana region, and the policy pursued by the ruling Kokand Khan Khudoyar Khan during the period of the threat posed by the Russian Empire